2022-RA-861-ESGO Transcriptome and genetic profile of epithelial ovarian carcinoma patients sensitive and resistant to platinum derivatives. (20th October 2022) - Hruda, Martin; Hlaváč, Viktor; Holý, Petr; Šeborová, Karolína; Václavíková, Radka; Mrhalová, Marcela; Černaj, Petr; Bouda, Jiří; Souček, Pavel; Rob, Lukáš
Abstract : Introduction/Background: Epithelial ovarian carcinoma (EOC) is known for high mortality due to diagnosis at advanced stages and frequent therapy resistance. This study aimed to address the complex profile of gene expression, germline variants and somatic mutational spectra, signatures, and copy number variations of resistant patients compared to sensitive ones patients and evaluated associations with their clinical data and survival. Methodology: RNA sequencing (RNASeq) in tumors, whole exome sequencing (WES) in DNA from blood and tumor tissue sample pairs of 50 patients with surgically resected EOC, and evaluation of platinum resistance status and complete follow up. Results: Coding transcriptome profile revealed significant associations of DUT expression with the presence of peritoneal metastases, upregulation of three genes (DDB2, HELQ, and MAD2L2), and downregulation of PRPF19 in platinum-sensitive compared to resistant patient's tumors. Results of WES analysis show that compared to sensitive patients, platinum-resistant ones have a significantly higher overall TP53 gene somatic mutational rate and a lower frequency of mutations in several genes from the Hippo pathway. We also confirmed a pivotal role of somatic mutations in homologous recombination repair (HRR) genes in the platinum sensitivity and favorable prognosis of EOC patients. Additionally, distinct mutational signatures and overall mutational load, somatic mutations in PABPC1, PABPC3, and TFAM co-segregated with the resistance status, high-grade serous carcinoma subtype, or overall survival of patients. Conclusion: Taken together, we assessed transcriptomic and genomic landscapes of prognostically different subgroups of EOC patients for further follow up studies focused on utilizing the observed associations in precision oncology. Supported by the Czech Health Research Council grant no. NU20–09–00174, the Ministry of Education, Youth and Sports, INTER-ACTION project no. LTAUSA19032 and Cooperatio program no. 207035, 'Maternal and Childhood Care' by 3rd Faculty Medicine, Charles University.